Bantuan Hukum Dalam Proses Pradilan Pidana di Indonesia - Karti Komalasari; I Made Minggu Widyantara; Ida Ayu Putu Widiati (Fakultas Hukum Universitas Warmadewa, 2019)
Paper entitled Legal Aid in Criminal Justice Process in Indonesia comes from Research sourced from the UDHR, a document that is morally binding. Some of the provisions regulate the general principles of law or those that describe the protection of human rights, and the frequent occurrence of the rights of suspects not informed by investigators. The problem (1) what is the process of granting Legal Aid in the criminal justice process? (2) What are the consequences for violating the right to Legal Aid in the criminal justice process? The approaches are legislative approach, factual approach, legal concept analysis approach, and approach through formulas or phrases. The sources of primary legal material in the form of binding and secondary legal materials include the opinions of scholarly scientific works in the collection of legal materials, such as the citation of books and legal journals collected and then processed and analyze. In order to provide signs for law enforcers in implementing material criminal law, legal assistance is regulated in article 54 of the Criminal Procedure Code and article 56 paragraph (1) The Criminal Procedure Code explicitly regulates the obligation of suspects to be accompanied by legal counsel 15 years and above, but if contrary to article 56 paragraph (1) of the Criminal Procedure Code, the judge examining the case must reject the prosecutor's charges, because it is contrary to article 56 paragraph (1). In accordance with the Supreme Court jur number 155/pid/1991, September 16, 1993.